Operasi penyampaian dakwah melalui radio: kajian kes di Kabupaten Wajo - Kaddas, Badruddin (2019)
The development of electronic media together with the progress of information technology. Development and engineering changes occur accelerated technology that is increasingly rising. The time span finding of radio and television black and white are necessary a long time. However, the further development of the invention of color television is starting to come to the discovery of internet communication technology, thus changing very fast. Radio as a medium of information has been used by an existing boarding school As'adiyah in Wajo South Sulawesi. The education system in boarding school is the system of non-formal education and informal education systems. Non-formal education system implemented in the form of boarding school recitation Boarding As'adiyah. This research seeks to analyze the operarations of delivering propaganda through radio, study to the Radio Suara As'adiyah Sengkang to get an overview of the effectiveness of the objective of religious information submitted through the Radio Suara As'adiyah Sengkang. The investigation into the evaluation to boarding school especially principles Radio Suara As'adiyah for opportunities and opposition in the dakwah broadcast by Radio. Propose improvement process of delivering propaganda througradio, especially Radio Suara As'adiyah. Research done. This study used a qualitative approach. Qualitative methods used in this research because of concerns that the investigation is very complex, dynamic and full of meaning. This method is used by researchers to get deep understanding of the methods of delivery, content material dakwah Radio Suara As'adiyah, how stature the source in this case clerics teacher / scholars who are at boarding school As'adiyah. Next will be in-depth study of the effectiveness of the delivery of the propaganda who served. The effectiveness of the delivery of the missionary is the announcer on the expertise, scientific credibility and stature of the speakers, the content of the material presented. The Radio suara As'adiyah have announcer that understand knowledge understand in hosting the event. Speakers are selected based on scientific and exemplary of the Bugis community gurutta call. The findings further that propaganda material presented is always based on the classic reference books to explain kontenporer.